Therapeutic Management of Notoedric Mange in Rabbits - Patel, Bhavika R; Chauhan, Vandip D; Prajapati, Ankit S; Joseph, Joice P; Vasava, Amrita A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Mange in rabbits is a highly contagious and a rising disease caused by different burrowing and non-burrowing mite species protozoon. Rabbits occasionally get infestated with Notoedres cati, which burrow the superficial layers of skin (Darzi et al., 2007). The mange infestation is widespread throughout the different parts of the world, with lesions first appearing on the lips and nose before spreading to the rest of the face. However, additionally crucial to zoonotic research, burrowing mites can cause humans to get dermatitis that is temporarily itchy. This mange spreads speedily through direct contact with skin or interaction with the environment (Panigrahi et al., 2016), and it can infect an immense number within a short duration of time. Only the adult female will pierce the skin and create a tunnel to deposit eggs. Adult male and older larvae stay on the skin surface. It takes two or three weeks to complete the life cycle from eggs to adulthood. If proper management practices are not implemented, this mange can cause severe pruritis and self-inflicted scratches that can result in secondary pyoderma, and it poses a serious threat to rabbit colonies. It is challenging to apply topical medication to eradicate a mite infestation, but ivermectin is simple to use and effective at clearing the skin of mange (McKellar et al., 1992). The present clinical case report explains Notoedric mange in two rabbits and its successful therapeutic management with the use of Ivermectin subcutaneously.